Robust validation of a generalised actuator disk CFD model for tidal turbine analysis using the FloWave ocean energy research facility. (May 2022) - Badoe, Charles E.; Edmunds, Matt; Williams, Alison J.; Nambiar, Anup; Sellar, Brian; Kiprakis, Aristides; Masters, Ian
Abstract: Coupled blade element momentum-computational fluid dynamic (BEM-CFD) approaches have been extensively used to study tidal stream turbine performance and wake development. These approaches have shown to be accurate when compared to tests conducted in tow-tanks or in regulated flumes with uniform flows across the turbine. Whilst such studies can be very useful, it is questionable as to what extent the results would differ in a larger scale environment where the flow is more representative of real-world conditions, being either unsteady or non-uniform. In this work, the effectiveness of a generalised actuator disk-computational fluid dynamics (GAD-CFD) approach in accurately capturing fluid-machine interaction for single and multiple tidal energy converters models is further assessed. A unique large-scale experimental facility, FloWave, has been used to conduct physical testing of three instrumented model tidal energy converters of rotor diameter 1.2 m under differing turbine layouts and realistic scaled environmental conditions. These large-scale tests provide a unique dataset against which this work's numerical simulations have been extensively validated. Comparisons between the tank and GAD-CFD approach show good agreement, particularly when comparing modelled to measured thrust, and enabled an evaluation of the effects of turbine spacing and arrangement on turbine performance and flow-field response.